PENILAIAN KETERAMPILAN PORTOFOLIO DALAM PEMBELAJARAN DI SEKOLAH - Herwani Herwani (Cross-border, 2022)
Portfolio assessment is an ongoing assessment based on a collection of information that shows the development of students' abilities in a certain period. The information can be in the form of student work from the learning process that is considered the best by students. In portfolio assessment contains important things, namely collection (storing), selection (sorting) and determination (dating), of a task (task). This portfolio assessment also has many benefits, objectives, assessment steps, assessment methods and advantages and disadvantages.